APLIKASI PEMBELAJARAN KRIPTOGRAFI HILL CHIPER DENGAN MENGGUNAKAN METODE COMPUTER BASED INSTRUCTION - PENNY SEPTIANI SIANTURI (STMIK KAPUTAMA, 2019)
Application of Information Technology in the current era of globalization is very important. Especially in our developing country, it is in dire need of various information and technology that can be applied to the progress of this nation. But to carry out this task, there are still many obstacles that must be faced both from the cultural conditions, the condition of the country and its human resources. This learning objective serves to facilitate the user in learning the material on Hill Chiper Cryptography and is an alternative in overcoming several problems such as limited time, and several other factors and can reduce the tedious learning atmosphere.Cryptography Hill Chiper Learning Application by using CBI Method (Computer Based Instruction) is a method developed with computer media, where the teaching method is directly to the user through how to interact in learning topics that have been packaged in a software application.Keywords: Learning, Cryptography Hill Chiper, Computer Based Instruction